Effects of the amount of C on machinability properties of Fe-Cu-C piece [Fe-Cu-C kompaktlarina katilan i̇lave C mi̇ktarinin i̇şlenebi̇li̇rli̇k özelli̇kleri̇ne etki̇si̇] - (:unkn) unknown (My University, 1999)
The powders added to material based on iron that is one application of the Powder Metallurgy change both the mechanical properties of product and also the facility of chip removal processing. In this study, the amount of the C in the Fe-Cu-C piece has been increased, while the amount of Cu is kept constant. Axial drilling force on the sintered piece has been measured in the specific conditions. The relation between the axial drilling force and the amount of C in the sintered piece has been examined. It has been seen that when the amount of C in the sintered piece increases axial drilling force increases.
Keywords: Machinability; Powder metallurgy